ANALYSIS OF MASS FLOW RATE IN COLD WATER INTO FLOW WITH HOT WATER OUTPUT TEMPERATURE IN SHELL AND TUBE HEAT EXCHANGER - Eko Susetyo Yulianto; Muhammad Aulia Febriandio Haadin (Asosiasi Dosen Muda Indonesia, 2022)
A heat exchanger is a device used to exchange heat and can usually function as a heater or a cooler. There are many types of heat exchangers available today. But the most widely used in industry is the shell and tube type heat exchanger. The shell and tube type heat exchanger has the advantages of being affordable, easy to maintain and has excellent heat transfer performance with a small volume. This paper aims to analyze the effect of mass flow rate on cold water inflow and hot water outlet temperature using water fluid in shell and tube heat exchanger. The design analysis that I did using the Solidworks 2019 software. This study only made a comparison by changing the mass flow velocity at the inflow of cold water with samples of 5 Kg/s, 10 Kg/s, 15 Kg/s, 20 Kg/s, 25 Kg/ s and 30 Kg/s and only sampled the hot water outlet temperature. The material used is stainless steel 321 on the shell and copper on the tube. The test results show that every increase of a multiple of 5 Kg/s there is a decrease in the average fluid temperature of 1.62 ℃ and the lowest temperature that can be achieved in this test is 52.33 ℃